The known geographical distribution of sand flies in the state of Rondonia, Brazil (Diptera: Psychodidae) - Biancardi, Ceclie M. B.; Arias, Jorge Ramon; Freitas, Rui Alves de; Castellón, Eloy Guilhermo (Acta Amazonica, 1982)
This study expands the knowledge of phlebotomine sand fly distribution in the state of Rondonia, Brazil. New state and country records are registered, bringing the total of known sand fly species in Rondonia to 78.